A Nurse’s Performance, Personality, and Situation Awareness in Fall Risk Prevention - Arindani, Farichah Septiana; Mustikawati, Bernadetta Indah; Chalidyanto, Djazuly (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
One indicator of a nurse’s performance evaluation regarding implementing patient safety programs in hospitals is the risk of a patient falling. An audit of fall risk prevention at Siloam Hospitals in Surabaya was used to evaluate nurses’ performance in preventing patient falls. The impact of personality and situation awareness characteristics on the nurse’s output performance in preventing fall risk was examined. A cross-sectional research design was used in the observational analytic research method. Forty-five nurses made up the total sample. The EPPS and SEAFAP questionnaire were the instruments used in the data analysis, which applied the linear regression test. The following personal characteristics have a p-value of 0.05 or less: Order (p-value 0.016), Autonomy (p-value 0.019), Affiliate (p-value 0.012), Succorance (p-value 0.012), and Nurturance (p-value 0.009). With a p-value of 0.040, situation awareness impacts output performance. Both overall personality and situation awareness have a p-value of 0.006 and influence output performance, respectively. Situation awareness and personality-based needs have an impact on output performance. To provide specific solutions to improve the probability of patients falling, the recommendations for enhancing the fall risk prevention programs can be carried out through discussion and interviews.